Electroconvulsive Therapy in Canada During the First Wave of COVID-19: Results of the "What Happened" National Survey. Issue 1 (14th September 2021) - Demchenko, Ilya; Blumberger, Daniel M.; Flint, Alastair J.; Anderson, Melanie; Daskalakis, Zafiris J.; Foley, Karen; Karkouti, Keyvan; Kennedy, Sidney H.; Ladha, Karim S.; Robertson, Jamie; Vaisman, Alon; Koczerginski, David; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The COVID-19 pandemic has disrupted the provision of essential and potentially life-saving procedural treatments such as electroconvulsive therapy (ECT). We surveyed ECT providers across Canada to understand how the first wave of the pandemic affected ECT delivery between mid-March 2020 and mid-May 2020. Methods: The survey was administered to ECT team members and decision makers at 107 Canadian health care centers with a focus on 5 domains: operations, decision-making, hospital resources, ECT procedure, and patient impact. Responses were obtained from 72 institutions, and collected answers were used to derive representative responses reflecting the situation at each ECT center. For specific domains, responses were split into 2 databases representing the perspective of psychiatrists (n = 67 centers) and anesthesiologists (n = 24 centers). Results: Provision of ECT decreased in 64% centers and was completely suspended in 27% of centers after the onset of the pandemic. Outpatient and maintenance ECT were more affected than inpatient and acute ECT. Programs reported a high level of collaboration between psychiatry and hospital leadership (59%) but a limited input from clinical ethicists (18%). Decisions were mostly made ad hoc leading to variability across institutions in adopted resource allocation, physical location of ECT delivery, and triaging frameworks. The majority of centers considered ECT to be aerosol-generating and incorporated changes to airway management. Conclusions: Electroconvulsive therapy services in Canada were markedly disrupted by the COVID-19 pandemic. The variability in decision-making across centers warrants the development of a rational approach toward offering ECT in pandemic contexts.